2017
DOI: 10.1161/circulationaha.117.027575
|View full text |Cite
|
Sign up to set email alerts
|

Early Use of N-acetylcysteine With Nitrate Therapy in Patients Undergoing Primary Percutaneous Coronary Intervention for ST-Segment–Elevation Myocardial Infarction Reduces Myocardial Infarct Size (the NACIAM Trial [N-acetylcysteine in Acute Myocardial Infarction])

Abstract: Australian New Zealand Clinical Trials Registry. URL: http://www.anzctr.org.au/. Unique identifier: 12610000280000.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
77
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(82 citation statements)
references
References 53 publications
2
77
0
3
Order By: Relevance
“…16 Given that cardiac injury and thrombosis are well established as potentially lethal complications in COVID-19, it is noteworthy that intravenously administered NAC has been shown to potentiate the vasodilator, anti-inflammatory and antiaggregatory effects of nitroglycerin, and this useful interaction has been translated into improving outcomes, such as in acute myocardial infarction, unstable angina and acute pulmonary edema. 68,69 Administration of NAC has been included among the possible strategies aimed at preserving endothelial function and limiting microthrombosis in severe forms of COVID-19. 70 In case of severe COVID-19 forms with pulmonary and/or systemic symptoms, intravenously administered NAC at the high doses that are commonly used in case of paracetamol intoxication, given at the first onset of chest symptoms, would be expected to play an adjuvant therapeutic role in combination with antivirals or other drugs.…”
Section: Discussionmentioning
confidence: 99%
“…16 Given that cardiac injury and thrombosis are well established as potentially lethal complications in COVID-19, it is noteworthy that intravenously administered NAC has been shown to potentiate the vasodilator, anti-inflammatory and antiaggregatory effects of nitroglycerin, and this useful interaction has been translated into improving outcomes, such as in acute myocardial infarction, unstable angina and acute pulmonary edema. 68,69 Administration of NAC has been included among the possible strategies aimed at preserving endothelial function and limiting microthrombosis in severe forms of COVID-19. 70 In case of severe COVID-19 forms with pulmonary and/or systemic symptoms, intravenously administered NAC at the high doses that are commonly used in case of paracetamol intoxication, given at the first onset of chest symptoms, would be expected to play an adjuvant therapeutic role in combination with antivirals or other drugs.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been studied in a variety of other conditions such as psychiatric illnesses, cardiac diseases, and chronic lung disorders [87] [88] [89]. NAC’s antioxidant properties are related to its role as a precursor for glutathione, the main intracellular antioxidant responsible for free radical and ROS scavenging, buffering, and many other cellular reactions [90].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, any compound known as strong antioxidant is believed to protect the cardiac tissues from MI. In fact, some experimental and clinical studies have shown that myocardial infarct size can be limited by increasing endogenous antioxidants and suppression of free radical generation 7 .…”
Section: Introductionmentioning
confidence: 99%